Building Bonds Through Certification: Collaborative Governance and Social-Economic Outcomes in Indonesia's Halal Ecosystem - Mansur; Abu Yasid; Rijalul Faqih (Universitas Negeri Surabaya, 2025)
The rapid growth of Indonesia's halal industry requires effective collaboration between regulatory, religious, and business actors. This qualitative study employed in-depth interviews with 42 stakeholders from BPJPH, MUI, and UMKM, supplemented by document analysis and focus group discussions. The tripartite collaboration builds institutional trust and creates shared values (social bonding), while certified UMKM report 15-25% price premiums and expanded market access (economic bonding). However, power asymmetries and regional disparities persist. Collaborative governance in halal certification strengthens the ecosystem's social and economic fabric, but requires more inclusive institutional designs. The study contributes to Islamic business literature by conceptualizing